1956
DOI: 10.1111/j.1365-2621.1956.tb16910.x
|View full text |Cite
|
Sign up to set email alerts
|

FREEZE‐DRIED MEAT. II. THE MECHANISM OF OXIDATIVE DETERIORATION OF FREEZE‐DRIED BEEFa

Abstract: Dehydrated meats of good organoleptic quality and functional properties can be produced in the form of steaks, chops, roasts, and stew meat by the method of freeze-drying (3,13). Since the primary value of freezedried meat, especially for the military forces, lies in its storage stability a t elevated temperatures, studies of its mechanism of deterioration become important.The mechanisms of deterioration of freeze-dried meat may be conveniently divided into those of oxidative and those of non-oxidative deterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

1956
1956
1994
1994

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…As was observed by Tappel (1956) and by Karel et al (1966)) oxygen can also be absorbed by proteins. This can account for up to SO-SO% of the total oxygen absorbed, especially at high temperatures.…”
Section: Oxidative Deteriorationmentioning
confidence: 53%
“…As was observed by Tappel (1956) and by Karel et al (1966)) oxygen can also be absorbed by proteins. This can account for up to SO-SO% of the total oxygen absorbed, especially at high temperatures.…”
Section: Oxidative Deteriorationmentioning
confidence: 53%
“…Oxidative changes in freeze-dried meats have been shown to involve the oxidation of bound lipids, e.g., phospholipids (Chipault and Hawkins 1%5), followed by the oxidation of glycerides. Tappel (1956) also concluded that ether-extractable lipids in freeze-dried meat absorbed only a small proportion of oxygen compared to nonether extractable fat. Therefore, although 20-carbon polyunsaturated fatty acids are concentrated by the extraction process, lipid oxidation in this fraction precedes the oxidation of 18-carbon fatty acids.…”
Section: Resultsmentioning
confidence: 99%
“…the compomids usually considered to be most susceptible to oxidation. Tappel (1956) EXPERIMENTAL reports also that potentially oxidizable In every instance the following basic canning procedure was followed. Freeze-dried slices taken was closed under 25 in.…”
Section: Introductionmentioning
confidence: 99%